Knowledge, Attitude and Education on Tourist Preparedness In The Tourist Locations Of Penatapan Sibolangit, North Sumatra In Facing Potential Natural Disasters - Azmi Nasution, Fachrul; Daulay, Harmona (Journal of Sumatera Sociological Indicators, 2023)
Indonesia as a country full of vulnerability from all aspects will never be separated from events called disasters. As well as causing a lot of loss and loss of life for the whole community, especially tourist groups, vulnerability due to ignorance to manage disaster risk is one of the factors that make people trapped in a situation when a disaster occurs. This is also used as the right moment for the community to start caring and also change their mindset on the importance of disaster management, or better known as Disaster Risk Reduction. This type of research uses explanatory research. The population in the study of all tourists at the Penatapan Sibolangit tourist location was 278 tourists. The research sample is 66 tourists. Data obtained by interview using a questionnaire and analyzed by logistic regression at CI: 95%. The purpose of this study was to analyze the influence of tourist knowledge, attitudes and education on tourist preparedness in dealing with disaster risks at tourist sites. The results of the study after statistical tests on the variables of knowledge, attitude and education of tourists have a significant relationship. It is hoped that the Karo Regency Government and the North Sumatra Provincial Government can provide support for the implementation of disaster education so that at all levels of education have the same understanding of the need for disaster preparedness to increase preparedness as an effort to reduce the risk of natural disasters.